Dimethyl fumarate: Regulatory effects on the immune system in the treatment of multiple sclerosis. Issue 7 (7th December 2018) - Hosseini, Arezoo; Masjedi, Ali; Baradaran, Behzad; Hojjat‐Farsangi, Mohammad; Ghalamfarsa, Ghasem; Anvari, Enayat; Jadidi‐Niaragh, Farhad
Abstract: Dimethyl fumarate (DMF) is an important oral treatment option for various autoimmune diseases, such as multiple sclerosis (MS) and psoriasis. DMF and its dynamic metabolite, monomethyl fumarate (MMF) are the major compounds that exert therapeutic effects on several pathologic conditions in part, through downregulation of immune responses. The exact mechanism of DMF is yet to be fully understood even though its beneficial effects on the immune system are extensively studied. It has been shown that DMF/MMF can affect various immune cells, which can get involved in both the naive and adaptive immune systems, such as T cells, B cells, dendritic cells, macrophages, neutrophils, and natural killer cells. It is suggested that DMF/MMF may exert their effect on immune cells through inhibition of nuclear factor‐κB translocation, upregulation of nuclear factor erythroid‐derived 2(E2)‐related factor antioxidant pathway, and activation of hydroxyl carboxylic acid receptor 2. In this review, the mechanisms underlying the modulatory functions of DMF or MMF on the main immune cell populations involved in the immunopathogenesis of MS are discussed. Abstract : Dimethyl fumarate (DMF) can suppress inflammatory immune responses and increase inhibitory cells. Therefore, it can be considered as a potent therapeutic for the treatment of multiple sclerosis.